1960-2015 Yılları Arasında Pop Sanatının Mimarideki Yansımaları - Göçek, Evren Ferdağ (Fen Bilimleri Enstitüsü, 2015)
Sanayi devrimiyle birlikte insan odaklı yapılmaya başlanan sanat ve kültür çalışmaları, İkinci Dünya Savaşı sonrası yaygınlaşan kitle iletişim araçları ile tüm dünyaya yayılma fırsatı bulmuş, değişen ekonomik dengelerin sonucunda ortaya çıkan kapitalizm, yarattığı pazarı desteklemek adına tüm sınıfsal farklılıkları ortadan kaldırmış, sanat ve kültür politikaları da kapitalizme hizmet etmeye başlamıştır. Kapitalizm yarattığı pazarı korumak ve büyütmek adına kullan-atçılığı özendirdiği bir tüketim kültürü yaratmış, bu kültür kitle iletişim araçlarının da gelişmesiyle popüler kültürü ortaya çıkarmıştır. Popüler kültür ve popüler kültür öğeleri, toplumların arasındaki sınıfsal ayrımı göz ardı edip, her kesime hitap eden tutumuyla hızlıca sevilip benimsenmiştir.  Popüler kültürün benimsenmesini sağlayan bir diğer faktör, aynı dönemde ortaya çıkan Post-Modernizm hareketi olmuştur. Modernizm’in radikal geometisine, katı kurallarına, tek diline isyan niteliğinde ortaya çıkmış olan Post-Modernizm, tüketime dayalı, günlük yaşayan, değer bilmeyen bunların yanı sıra çok sesliliğe inanan bir kültür yaratarak popüler kültürü desteklemiş, kitle iletişim araçları sayesinde, bu tutumlar oldukça geniş alanlara yayılmıştır. Popüler kültürü destekleyen, tüketime dayalı yaşam koşulları özellikle ekonomilerde sıkıntılar yaratarak sanat olaylarını etkilemiştir. Önceden yalnızca elit ve entelektüel kesime hitap eden sanat, değişen ekonomik dengeler doğrultusunda kullandığı malzemeler ile her kesimin yönettiği bir olgu haline dönüşmüştür.  Bu doğrultuda ortaya çıkan Pop Sanatı, malzemesini her gün tüketilen sıradan ürünlerden, bu ürünlerin markalarından, her gün kitle iletişim araçları vasıtasıyla maruz kaldığımız, popüler kültürün ortaya çıkardığı film yıldızları ve şarkıcılardan oluşturarak, bunları Pop sanatçısının kendi üslubuyla kattığı ironiyle harmanlayıp topluma geri sunmuştur. Pop Sanatı, döneminde olan toplum ve kültür olaylarını birebir topluma geri aktaran bir akım olduğu için, Post-Modernizm gibi açık sözlü bir akımla birlikte gelişme gösterebilmiştir.  Pop Sanatı’nın mimariye yansımaları da benzer çıkış noktalarına dayanmaktadır. Pop Mimari, Post-Modern Mimarlık’ın benimsediği bir çok tutum içinden kendi kurallarına en yakın olanları süzgeçten geçirerek, bir akım olarak oluşmasa da mimarlıkta kendi dilini yaratmıştır. Post-Modern Mimarlık’ın iletişim kurmaya yönelik çoğulcu, ironiyi seven anlayışına ek olarak popüler kültür öğelerine yer vermesi, alışılageldik öğeleri alışılagelmedik şekilde kullanımı ile mimaride farklılıklar yaratmıştır. 1960’lardan günümüze dek örnekleri görülen Pop Sanatı’nın mimarideki yansımaları, yıllar geçtikçe değişen teknoloji ve kültürel koşullar doğrultusunda sürekli bir dönüşümde olsa da yapılarda temel öğelerini her zaman ön planda tutmuştur.

After the industrial revolution, art and cultural works were done for humans and for life, and with the help of mass communication products, they spread all around the world. Capitalism appeared with the upset of the balances on economy, and fed from consumerism. With the help of capitalism, the gap between highbrow and lowbrow cultures disappeared. The differentiation between social classes started disappearing, so art and culture politics started to serve for the sakes of capitalism, not for highbrow culture anymore. To be able to spread and enlarge the market, capitalism created single-use things, cheap materials, fake, banal, vulgar goods for society to use and consume, this movement led to creation of popular culture. Popular culture was embraced by community so fast, because it ignored the differentiation between  highbrow and lowbrow cultures and address to every human-being who is part of the community they live.  Correspondingly, Post-Modernism movement showed up, while popular culture was being spread all around the world. Post-Modernism has been applied to art and architecture, which reacted against the radical geometric forms and strict rules of Modernism.  Post-Modernism was marked by culture that based on consumption, carpe diem and believe in composition of different voices and these intentions overlap with the intentions of popular culture. Through the similar aims, Post-Modernism and popular culture supported each other and with the help of mass media, they both spread widely. With the change of living conditions that depended on consumption, popular culture affected the art and architectural works, starting from America, spread all around the world. Through this progress, art became a product for consumption culture. With the upset of economical balance, art works changed concept and materials, so that they didn’t address to highbrow only anymore.  In this direction, Pop Art was born, using everyday consumed products, brandings, movie stars and singers and all those materials that created with the help of mass communication tools. The Pop Artists blend these materials with their own style, adding irony and giving back to community to use and have fun. Pop Art has developed with Post-Modernism because it transferred the community and culture events back to society in the same way it has happened.  Pop Art tendencies on architecture depend on similar origin. Pop Architecture had been eliminated the Post-Modern manners that were close to its own rules, and created its own language, even Pop Architecture has never been an ism. Plural, ironic attitude, communicative approach, including popular culture elements, using familiar elements in an unfamiliar way have been the best reflections on architecture of Post-Modernism. Pop Art tendencies on architecture from 1960’s until today change in coordination with new technology and new cultural principles but it always conserves its main principles. In this study, Pop Art tendencies on architecture considered decade by decade since 1960’s, because 60’s have been a milestone for technological and cultural events. Right after World War II and its effects all around the world, cities, cultures, and communities started to reshape and regenerate. This progress was the main incident of 50’s, but it showed its clear reflections on 60’s.  The research started with the formation of Post-Modernism and its effects on architecture. The first part, focuses on the reasons of how Post-Modern movement to occurred against Modernism. Supported with the leading architectural historian’s literature, the evaluation Post-Modern Architecture clarified. The next step was to explain popular culture and consumption culture, and how the both reflected economical and artistic events. Followed by the definition of Pop Art, the research focused on how technology, economy and cultural approaches affected an art movement. Explaining the visions of the leading Pop Artists, make it clear for understanding the Pop tendencies on architecture.  After the evaluation of historical topics, the way of how the Pop Art reflected on architecture has been enlightened and the examples have been given on the works produced after the studies on history of architecture during 1960-2015. The buildings have been chose according to their relevance of the theoretical surveys and researches that have been done.
Pop Art Tendencies In Architecture Between 1960-2015
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: POP SANATI; MİMARLIK; MİMARLIK TARİHİ; POP MİMARİ; POPÜLER KÜLTÜR; POP ART; ARCHITECTURE; HISTORY OF ARCHITECTURE; POP ARCHITECTURE; POPULAR CULTURE